The Theory of Ratio Scale Estimation: Saaty's Analytic Hierarchy Process - Harker, Patrick T.; Vargas, Luis G. (Management Science, 1987)
The Analytic Hierarchy Process developed by Saaty (Saaty, T. L. 1980. The Analytic Hierarchy Process. McGraw-Hill, New York.) has proven to be an extremely useful method for decision making and planning. However, some researchers in these areas have raised concerns over the theoretical basis underlying this process. This paper addresses currently debated issues concerning the theoretical foundations of the Analytic Hierarchy Process. We also illustrate through proof and through examples the validity or fallaciousness of these criticisms.